Pengaruh Konsumsi Jus Nanas terhadap Tinggi Fundus Uteri pada Ibu Postpartum : Studi Literatur - Nurita, Suci Rahmani; Jamilah, Jamilah; Nurbaiti, Nurbaiti; Perwitasari, Tuhu (Universitas Baiturrahim, 2024)
The process of decreasing the height of the uterine fundus begins since the birth of the placenta if this process fails or there is a problem called subinvolution which can trigger bleeding. One effort to prevent subinvolution is to provide complementary therapy with pineapple juice. Pineapple contains a lot of bromelain enzymes that are not found in other fruits. Bromelain enzymes are one of the enzymes that have proteolytic properties that will shorten the uterine fundus muscles so that there is a decrease in the height of the uterine fundus (HUF). This study aims to determine the effect of pineapple juice on the height of the uterine fundus in postpartum mothers. The research method used is a literature review. The source of literature search uses the Google Scholar database. The results of the literature study obtained 5 journals that met the inclusion criteria where the results of the data analysis showed that before giving pineapple juice, a HUF of 13.70 cm was obtained and after giving pineapple juice for 7 days, the HUF measurement results were 5.0 cm. There is a difference in the average decrease in HUF before and after being given pineapple juice (Ananas Comosus (L) Merr) between the experimental group and the control group. The difference in mean value is 2.06 with a significance of P-value = 0.000. Giving pineapple juice is effective in helping to accelerate the process of uterine involution and reducing the height of the uterine fundus. Midwives should provide education and information about the benefits of pineapple juice in accelerating uterine involution after delivery.